Eradication of HIV and Cure of AIDS, Now and How? - Zhang, Jie Lin; Crumpacker, Clyde (Frontiers in Immunology, 2013)
Recent studies have highlighted the importance of eradication of human immunodeficiency virus (HIV) and cure of acquired immunodeficiency syndrome (AIDS). However, a pivotal point that the patient immunity controls HIV reactivation after highly active anti-retroviral therapy (HAART, or combination anti-retroviral therapy, cART) remains less well addressed. In spite of the fact that both innate and adaptive immunities are indispensable and numerous cells participate in the anti-HIV immunity, memory CD4 T-cells are indisputably the key cells organizing all immune actions against HIV while being the targets of HIV. Here we present a view and multidisciplinary approaches to HIV/AIDS eradication and cure. We aim at memory CD4 T-cells, utilizing the stem cell properties of these cells to reprogram an anti-HIV memory repertoire to eliminate the viral reservoir, toward achieving an AIDS-free world.